Impact of Road Infrastructure Expenditures on Commercial Property Investment Returns in Abuja, Nigeria - Yakubu, S.; Usman, M. M. (International Journal of Real Estate, 2025)
Road infrastructure plays a critical role in shaping urban development and real estate investment performance. However, despite increasing government spending on transportation infrastructure in Nigerian cities, limited empirical research has specifically examined how road infrastructure expenditure influences commercial property investment returns over time in Abuja. Previous studies have largely focused on general infrastructure conditions or relied on cross-sectional perception-based assessments of property value changes without isolating the direct effect of road infrastructure spending. This creates a research gap in understanding the extent to which road infrastructure investment contributes to commercial real estate performance in Abuja. This study aims to examine the relationship between Government Road infrastructure expenditures and commercial property investment returns in Abuja, Nigeria, between 2020 and 2024. The objectives are to analyze trends in road infrastructure expenditure within the study period; assess trends in commercial property investment returns; and determine the statistical relationship between road infrastructure spending and commercial property returns. A quantitative research methodology was adopted using secondary data obtained from the Federal Capital Development Authority (FCDA), the Federal Ministry of Works and Housing and professional real estate market reports. Descriptive statistics were used to examine expenditure and return trends, while inferential statistical techniques including the Pearson product–moment correlation and linear regression analysis were applied to determine the strength and predictive relationship between road infrastructure expenditure and commercial property investment returns. The results reveal a strong and statistically significant positive correlation between road infrastructure spending and commercial property investment returns (r = 0.74, p < 0.01). Regression analysis indicates that road infrastructure expenditure explains approximately 55% of the variation in commercial property investment returns during the study period. The study concludes that increased road infrastructure investment significantly enhances commercial property investment performance by improving accessibility and stimulating commercial activity. It therefore recommends sustained and strategically targeted road infrastructure development integrated with urban land-use planning to promote sustainable real estate growth in Abuja.
Keywords: Road infrastructure; infrastructure expenditure; commercial property investment; investment returns; urban development